2004
DOI: 10.1016/j.foreco.2003.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of heartrot in harvest-age Acacia mangium in Indonesia, using a rapid survey method

Abstract: The potential to use plantation-grown Acacia mangium for solid-timber products is limited by heartrot, caused by decay fungi. A rapid method of surveying logs stacked in the plantation following harvest was developed which is an alternative to timeconsuming whole tree destructive assessments. Logs were randomly chosen from the stacks using a transect method, the cutends of the logs were assessed (2199 logs in total) and heartrot severity was scored on a 1-4 scale. Surveys of harvest-age A. mangium were complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 4 publications
0
19
0
5
Order By: Relevance
“…The seed source of trees grown in these regions and descriptions of the soil and climate, have been described elsewhere. 4 Freshly harvested logs of trees with and without heart rot were sampled.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed source of trees grown in these regions and descriptions of the soil and climate, have been described elsewhere. 4 Freshly harvested logs of trees with and without heart rot were sampled.…”
Section: Plant Materialsmentioning
confidence: 99%
“…1 One of the major impediments to using A. mangium for solid wood products is the prevalence of heart rot, which is fungal decay of heartwood in living trees. [2][3][4] Field studies have revealed that while A. mangium trees are susceptible to heart rot, Acacia auriculiformis and hybrids between the two species appear to be resistant. 5,6 Smaller branch sizes of A. auriculformis have been suggested as a basis for the lower incidence of heart rot 5 because infection is established mostly through dead stubs and branches.…”
Section: Introductionmentioning
confidence: 99%
“…Pedley]. Foi relatada pela primeira vez por Gibson, em 1981(Lee, 2002, em plantas de 33 meses, na Malásia, e também em Bangladesh, Índia, Indonésia, Papua Nova Guiné, Tailândia e Vietnã (Basak, 1997;Old et al, 2000;Lee, 2002;Barry et al, 2004).…”
Section: Heartrot In Homogeneous Stands Of Acacia Mangiumunclassified
“…Rimbawanto (2002) and Barry et al (2004) reported that around 80% of plantations in Indonesia managed by state and private companies are composed of A. mangium. Around 1.3 million ha of A. mangium plantations have been established in Indonesia for pulpwood production (Ministry of Forestry 2003).…”
Section: Introductionmentioning
confidence: 99%